Web Hackers Or Culture Transmitting Agents: Internet And Consumption Patterns Of Cultural Goods Among Algerian Students - Leila Hammoud (International Journal of Social Communication, 2021)
Piracy invests digitized cultural products and allows the entanglement between the piracy of cultural products on Internet and current cultural practices The study aims at interviewing privileged witnesses to the cultural products piracy practice in order to understand their roles as transmitting agents of culture and to grasp the pirate user’s own culture and its representations of the practice of piracy of cultural property,